More than a mere sequence: predictive processing of wh-dependencies in early bilinguals - Kljajevic Vanja (De Gruyter, 2016)
The purpose of the present study was to determine whether early bilingual Basque-Spanish speakers, who acquired Spanish by the age of 5, comprehend Spanish wh-dependences as effortlessly as native Spanish speakers. Given that Basque and Spanish are structurally different languages, we hypothesized that predictive processing strategies from the first language (L1) would interfere with predictive processing strategies in the second language (L2). More specifically, since Basque overtly marks the semantic role of agent/subject position, whereas Spanish overtly marks the role of patient/object position, we looked at whether the difference in overt marking of semantic roles would affect comprehension of subject vs. object quien “who” and qué “which” direct and embedded questions as well as subject vs. object relative clauses introduced by qué. The main finding of the study is that overall early Basque-Spanish bilinguals needed more time for the comprehension of wh-dependencies in Spanish compared to native Spanish speakers, as indicated by statistically significant group differences in response times in 9 out of 10 conditions. The results of this exploratory study indicate that a difference in overt marking of semantic roles between the two languages affects the ease of processing of Spanish wh-dependencies in early Basque-Spanish bilinguals, interfering with their ability to make native-like predictions in L2.